D6 high-quality expanded blastocysts and D5 expanded blastocysts have similar pregnancy and perinatal outcomes following single frozen blastocyst transfer - Hu, Juwei; Zheng, Juan; Li, Jie; Shi, Haiyue; Wang, Hua; Zheng, Bangxu; Liang, Kun; Rong, Chunhao; Zhou, Liming (Frontiers in Endocrinology, 2023)
Objective: We compared the pregnancy and neonatal outcomes between expanded blastocysts vitrified on D5 versus D6 following single frozen blastocyst transfer. Methods: Clinical data on 7,606 cycles of frozen-thawed blastocyst implantations were retrospectively analyzed. Depending on whether blastocysts were vitrified on D5 or D6 and the transferred blastocysts, the blastocysts were divided into 6 groups: HQB-D5, HQB-D6, 4XC-D5, 4XC-D6, 4CX-D5, and 4CX-D6 groups. The differences in clinical pregnancy rate, live birth rate, first trimester abortion rate, preterm birth rate, gestational age, birth weight, and sex ratio at birth among the groups were compared. Results: Our study showed that there was no difference in pregnancy and perinatal outcomes between the delayed formation of D6 high-quality expanded blastocysts and D5 expanded blastocysts, whether they were high-quality blastocysts or not. For low-quality blastocysts, the clinical pregnancy rate of D5 was higher than that of D6, and D5 was also better than D6 in live birth rate for those with inner cell mass rating B or above, while there was no difference between D5 and D6 for those with inner cell mass rating C. Conclusion: Based on our research, we suggest that when we are developing the implantation strategy, we give priority to the selection of high-quality expanded blastocysts, regardless of D5 and D6, whose clinical outcomes are not different. For low-quality blastocysts, D5 expanded blastocysts are preferred for transfer.